4f amplified in-line compressive holography - Wu, Xiaoyan (2014)
Compressive holography is a combination of compressive sensing and holography. In this paper, an approach to expand the amplification ratio and enhance the axial resolution in in-line compressive holography is proposed. Firstly the basic principle of 4f amplified in-line compressive holography is described. Next the feasibility of reconstructing object and analysis of reconstruction quality is verified. Finally, both simulated and real experiments on multilayer objects with non-overlapping and overlapping patterns are demonstrated to validate the approach.